TriÂplanar balancing optimization of a double crankÂrocker mechanism for shaking forces and shaking moments reduction - Albaghdadi, A.M. (Estonian Academy Publishers, 2021)
In this study, a new optimization approach is introduced to reduce vibration exerted on a double crankÂrocker mechanism. A dynamic analysis based on planar methods of this mechanism is suggested, and formulation of shaking forces and shaking moments inducing vibration on this system is presented. A twoÂstep optimization technique is suggested to study system sensitivity to the components of shaking forces and moments to enhance the mechanismâs balancing process. This leads to identification of the most dominant parameters which are then used to formulate the objective functions of effective optimization. Each objective function is studied for each individual case, after which the outcome results of the mechanismâs balancing optimization are introduced and discussed. Â© 2021, Estonian Academy Publishers. All rights reserved.